Evaluation of freshness parameters in commercial retail eggs in the region of Junin - Lucas, J. Raúl (2020)
The Peruvian central Andes require interventions to ensure the safety of superfoods such as eggs because the altitude of this region has not allowed the development of poultry production, so most eggs are transported from sea level which could affect their shelf life. The aim of this work was to evaluate the freshness of eggs retailed in the Peruvian central highland. The proportion of eggs with deteriorated freshness was determined through the analysis of the Haugh units (HU), the yolk index (YI) and the pH of the white and yolk in 145 commercial eggs from the provinces of Jauja and Huancayo. The 13.8% of the third quality eggs simultaneously presented all the freshness parameters deteriorated and therefore exceeded the shelf life. These eggs would be showing a reduction in their properties and, in addition, could be more prone to microbial invasion.